Co-Calcination of Bauxite Residue With Kaolinite in Pursuit of a Robust and High-Quality Supplementary Cementitious Material - Peys, Arne; Hertel, Tobias; Snellings, Ruben (Frontiers in Materials, 2022)
The present paper investigates the potential of co-calcination with kaolinite as a sector-wide solution for the transformation of bauxite residue (BR) into an effective supplementary cementitious material (SCM). Bauxite residues from eight alumina refineries were co-calcined with 30 wt% of kaolinite at 750 °C. SCMs with moderately-high reactivity were obtained. Mortars with 30 wt% replacement of Portland cement by co-calcined bauxite residue had relative strengths of 73±4 %, 87±4 % and 88±2 % after 2, 7 and 28 days compared to a CEM I reference mortar. Co-calcination reduced the mobility of heavy metals significantly. The negative effect on workability that some BRs with higher contents of free sodium content exhibited was mitigated by co-calcination. This positive effect was also observed after calcination with 10 and 20 wt% of kaolinite. The same was found for the positive effect on the leaching of heavy metals. The reactivity and contribution to strength development was shown to scale linearly with the kaolinite dosage. Most bauxite residues require only 20 wt% substitution by kaolinite to reach reactivity and performance targets. The inherent reactivity of the bauxite residue mainly stemmed from the desilication products sodalite and cancrinite. During co-calcination, the sodium-containing phases reacted with kaolinite, delivering an SCM with high reactivity and a low free sodium content.